(3GdYed HGdQHY GdeLjH (B( (3hgh GdQHY GdPi ajg Gdejd hGdLjH(B)s
(3ChdgG (B:s
(3hgh CQHYI hYTQhf HGHkG (B: (3GdHGH GdChd ai eYQaI CLRGA GdCQJaGY Cf CYQac hGTQM dc GdYde HGdQHY GdeLjH ai cd ehVY aTQMJ dc eG jSgd eYQaJg hJQcJ eG jUYH Ydjc MaXg s
(3BNQgG (B:s
(3JONd GdTeS HQL GdOdh ai JSYI YTQ ef WhHI dGjcGO gPG Gdbhd jNJd Ef de jcf ai Gdjhe hEdG cGf ai Gdjhe GdPi jdjg hGddg CYde Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs